2009
DOI: 10.1007/s11548-009-0282-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CyberDome, a novel 3-dimensional dome-shaped display system, on laparoscopic procedures

Abstract: The novel 3DD system is a promising tool for providing depth perception with high resolution to laparoscopic surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…In our study, we did not find any difference in terms of the performance of tasks between the two imaging systems in different experience groups. Our study was based on the evaluation of completion time of ten surgical tasks that have been previously reported, from simple to complex, and the number of mistakes made during the performances was used as an objective criteria [3,4]. We found that all participants completed the tasks of transferring beads and passing two circles with the needle in a shorter time with 3D LVS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, we did not find any difference in terms of the performance of tasks between the two imaging systems in different experience groups. Our study was based on the evaluation of completion time of ten surgical tasks that have been previously reported, from simple to complex, and the number of mistakes made during the performances was used as an objective criteria [3,4]. We found that all participants completed the tasks of transferring beads and passing two circles with the needle in a shorter time with 3D LVS.…”
Section: Discussionmentioning
confidence: 99%
“…Monocular cues are used in 2D laparoscopy to compensate for this lack of depth perception, and through experience, processing of monocular cues can be learned and depth perception might be improved [3,18,19]. Laparoscopic surgeons require extensive experience to overcome these handicaps of 2D display [4]. Additionally, the risk of injury increases due to potential misperception of the originally 3D structure of human anatomy in the 2D system [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…С появлением камер высокого разрешения и высо-кокачественных экранов эндохирургия претерпела значительные изменения в области визуализации внутренних объектов [1][2][3]. Тем не менее обычная лапароскопия все еще имеет ограничения.…”
unclassified